The First Joint European Partial-G Parabolic Flight Campaign at Moon and Mars Gravity Levels for Science and Exploration - Pletser, Vladimir; Winter, Josef; Duclos, Fabienne; Bret-Dibat, Thierry; Friedrich, Ulrike; Clervoy, Jean-Francois; Gharib, Thierry; Gai, Frederic; Minster, Olivier; Sundblad, Patrik (Microgravity science and technology, 2012)
Aircraft parabolic flights provide repetitively short periods of reduced gravity and are used to conduct scientific and technology microgravity investigations, to test instrumentation prior to space flights and to train astronauts before a space mission. Since 1997, ESA, CNES and DLR use the Airbus A300 ZERO-G, currently the largest airplane in the world for this type of experimental research flight. This mean is managed by the French company Novespace. Since 2010, Novespace offers the possibility of flying reduced gravity levels equivalent to those on the Moon and Mars achieved repetitively for periods of more than 20 s. ESA, CNES and DLR issued an international call for experiments inviting European Scientists to submit experiment proposals to be conducted at these partial gravity levels. The scientific objectives are on one hand to obtain results at intermediate levels of gravity (between 0 and 1 g) allowing a better study of the influence of gravity, and on the other hand to give them some elements to prepare for research and exploration during space flights and future planetary exploration missions. ESA, CNES and DLR jointly organised in June 2011 the first Joint European Partial-G Parabolic Flight campaign with 13 experiments selected among 42 received proposals. Parabolas were flown during three flights providing micro-, Moon and Mars gravity levels with duration typically of 20 s, 25 s and 32 s with a mixed complement of investigations in physical and life sciences and in technology. The paper presents the approach taken to organise this campaign and the 13 selected experiments with some preliminary results are presented to show the interest of this unique research tool for microgravity and partial gravity investigations.